Carbon Strategy, Political Connection and Carbon Performance: Evidence from Polluting Industries - Kawulur, Hisky Ryan; Saraswati, Erwin; Ghofar, Abdul; Prastiwi, Arum (International Journal of Energy Economics and Policy, 2024)
The increase in carbon emissions poses a significant threat to corporate performance, necessitating appropriate mitigation measures and strategies. However, the role of carbon strategies and political connections in enhancing carbon performance remains a subject of debate. Hence, this research examines the relationship between carbon strategies, types of carbon strategies, and political connections with carbon performance in polluting industries in Indonesia. The sample consist of 192 firm-year companies during 2016-2022. This study found: First, a combination of various types of carbon strategies will drive improvements in carbon performance. Second, compensation mechanisms can mitigate carbon emissions excesses. Third, the implementation of mitigation measures through innovation in processes and products can reduce carbon emissions. Fourth, political connections exacerbate corporate carbon performance. The research outcomes contribute to companies by providing insights into mitigation measures that can be undertaken to reduce carbon emissions and promote the achievement of Indonesia’s vision of net-zero emissions.